Effect of molybdenum/sulfur-induced copper deficiency upon enzyme levels and reproduction in heifers - Arthington, J.D.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To evaluate the effects of molybdenum (Mo)- and sulfur (S)- induced copper (Cu) deficiency, 99 prepubertal heifers were allotted into two groups. Treated heifers (n = 72) were fed a grass hay naturally high in Mo (Mo = 8 ppm and Cu = 3.2 ppm). Sulfur was supplemented to achieve a dietary level of .3%. Control heifers (n = 27) received a grass hay with normal levels of Mo (Mo = .47 ppm and Cu = 1.5 ppm). Copper was supplemented to achieve a dietary level of 8 ppm. Diets were fed for a period of 163 d. Liver samples were collected and analyzed for total Cu. Copper-containing enzyme activity (ceruloplasmin and Cu,Zn-superoxide dismutase [Cu,Zn-SOD]), and progesterone were measured in blood serum. Heifers in the treated group had lower concentrations of liver Cu and decreased ceruloplasmin activity, with no differences noted in Cu,Zn-SOD activity or onset of puberty. No difference was detected in first-service conception rate following artificial insemination (AI). Overall AI pregnancy rate tended to be higher for control heifers.
Keywords: Beef; Heifers; Copper; Ceruloplasmin; Cu,Zn-SOD; Reproduction